UJI BAKTERI Coliform PADA KUE BASAH DI PASAR SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU DAN POTENSINYA SEBAGAI RANCANGAN MODUL PADA MATERI EUBACTERIA DI SMA KELAS X - Cahyati, Nindy Inka; Sayuti, Irda; Zulfarina, Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the presence of Coliform bacteria in traditional cake that are sold at Simpang Baru Market in Tampan District, Pekanbaru from April 2019 to November 2019. This research is an experimental study consisting of research on Coliform bacteria in the Laboratory and the module design. The research samples were taken by random purposive sampling method which was taken each of 2 samples from 8 traditional cake traders in Simpang Baru market in Tampan District, Pekanbaru based on predetermined criterias. Coliform bacteria were tested by the Most Probable Number (MPN) method which consisted of three stages, which were persumtive test, confirmative test and completed test using different growing media and incubated at 37oC for 2x24 hours. The results were from 16 samples, the highest MPN Index Value was ongol-ongol at location 8 which has >979 cells / 100 ml and the lowest was ongol-ongol at location 3 and ubi gula at location 6 was 17 cells / 100, and from 16 samples in total, 14 samples contained Coliform bacteria from the genus Enterobacter. The results of the study can be used as an example of the learning module of the concept of Eubacteria in High School Biology Subjects in Class X.Key Words: Coliform, Kue Basah, Module Design